Amelioration of the nephrotoxic effect of potassium dichromate by whey protein and/or Nigella sativa oil in male albino rats - Samir A. E. Bashandy, Mohamed M. Amin, Fatma A. Morsy, Salma A. El-Marasy (Journal of Applied Pharmaceutical Science, 2016)
Even though whey protein complex derived from milk, is being touted as a functional food with a number of health benefits, so far its full mechanistic effect has not been deeply explicated, which is the target of this study. For this reason, we observed the 2 months protection influence of whey protein (100 & 200 mg/kg, p.ob.wt.) and/or oil of Nigella sativa (5ml/kg, p.ob.wt.) against intoxicated rats with single dose of potassium dichromate (30mg/Kg, I.P) at the end of protection period. On the biochemical level, whey protein and/or oil of Nigella sativa were changed the potassium dichromate renal toxicity consequences, where it showed a significant improvement in the creatinine, urea, protein, uric acid and sodium levels. While in the tissue level (Kidney), it revealed a significant enhancement in reduced glutathione (GSH), catalase and superoxide dismutase (SOD) enzymes as compared to nephrotoxic group. Moreover, whey protein and/or oil of Nigella sativa reduced the elevation of malondialdehyde (MDA) and inflammatory mediators like tumor necrotic factor-alpha (TNF-α) and nitric oxide (NO) induced by potassium dichromate and alleviation the histopathological changes caused by the intoxication. These results give a new vision into the hopeful mechanisms that modulated numerous factors induced renal injury.
Keywords: Whey protein, oil of Nigella sativa, potassium dichromate, Nephrotoxicity.